Thyroid Function, Cardiac Risk Assessment Profile and Hematological Changes During HIV Infection and AIDS Patients - Pasupathi, Palanisamy; Manivannan, Perisamy; Manivannan, Uma; Deepa, Mathiyalagan (Journal of Medicine, 2010)
Background: The aim and objective of this study was to investigate the level of serum lipids and thyroid hormones status in HIV infection and AIDS patients. Methods: The population consisted of 150 subjects divided into three groups; among HIV infected patients fifty cases, AIDS patient’s fifty cases and an equal numbers of age- and sex-matched healthy subjects were investigated. Results: In this study, we observed the level of serum lipids significant changes occur in AIDS patients compare to HIV infection and healthy subjects. There were no significant differences in total TT4 concentrations among the AIDS patients when compared to HIV infection and normal healthy subjects. A measured FT4 concentration was slightly but significantly decreased in HIV /AIDS patients. Total T3 concentrations were normal in HIV infected patients, but slightly decreased in AIDS; more important, T3 level was decreased in AIDS patients. The level of FT3 concentration was slightly but significantly increased in HIV infected and significantly decreased in AIDS patients. As all TSH levels were within the normal range; however, there was a small but significantly increase in TSH levels in AIDS, and there was a trend toward an increase in TSH levels in AIDS compared with controls. Conclusion: Thyroid dysfunction is frequent in HIV infection and with progression of disease there is a primary hypothyroid like stage that occurs in patients with HIV infection. TT3, FT3, FT4 and serum TSH can be used as a surrogate marker of the progression of the disease. Key words: HIV; AIDS; CD4+ cell count; Thyroid function test; Lipids; Hematological Test DOI: 10.3329/jom.v11i2.5455 J MEDICINE 2010; 11 : 131-136